The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/pat.3804
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of polycarbonate/acrylonitrile butadiene styrene/multiwall carbon nanotube nanocomposites under impact loading

Abstract: In this study, the effect of polycarbonate (PC)/acrylonitrile butadiene styrene (ABS)‐reinforced multiwall carbon nanotube (MWCNT) nanocomposites under a high‐velocity impact was investigated. PC/ABS (70/30 w/w)/MWCNT nanocomposites containing 1, 2, and 4 wt% were used to manufacture samples for this study. The samples were fabricated in sheet form with 100 × 100 mm dimensions and tested by gas gun for high‐velocity impact tests. The experimental results indicate that the energy absorption, limit velocity, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Similarly, Pour et al recorded a 30% increase of Young's modulus in 30/70 w/w ABS/PC blends, when 3 wt% GNP was added. Taheri et al observed a 103% increase of this property in 30/70 ABS/PC blend reinforced with 2 wt% MWCNTs, while Wegrzyn et al found that stiffness of 15/85 w/w ABS/PC blend increased 15–20% with CNTs load until 3.0 wt%. The different degree of improvement is maybe justified by different nanocomposite preparation process, as in first case nanocomposites were prepared by mixing all components in appropriate amounts in an internal mixer, extrusion and compression‐molding, while in the second one nanocomposites were formed with pre‐dispersed MWCNT masterbatch in a twin screw extruder and injection molding.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Pour et al recorded a 30% increase of Young's modulus in 30/70 w/w ABS/PC blends, when 3 wt% GNP was added. Taheri et al observed a 103% increase of this property in 30/70 ABS/PC blend reinforced with 2 wt% MWCNTs, while Wegrzyn et al found that stiffness of 15/85 w/w ABS/PC blend increased 15–20% with CNTs load until 3.0 wt%. The different degree of improvement is maybe justified by different nanocomposite preparation process, as in first case nanocomposites were prepared by mixing all components in appropriate amounts in an internal mixer, extrusion and compression‐molding, while in the second one nanocomposites were formed with pre‐dispersed MWCNT masterbatch in a twin screw extruder and injection molding.…”
Section: Resultsmentioning
confidence: 99%